2003
DOI: 10.1128/jvi.77.9.5428-5438.2003
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the Membrane-Associated Hepatitis C Virus Protein NS4B

Abstract: Hepatitis C virus (HCV) belongs to the Hepacivirus genus in the Flaviviridae family. Among the least known viral proteins in this family is the nonstructural protein NS4B, which has been suggested to be a part of the replication complex. Hydrophobicity plots indicate a common profile among the NS4B proteins from different members of the Flaviviridae family, suggesting a common function. In order to gain a deeper understanding of the nature of HCV NS4B, we have determined localization and topology of this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
220
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(238 citation statements)
references
References 55 publications
13
220
1
3
Order By: Relevance
“…NS4B: Inducer of a Membrane Scaffold for the Viral RC?-TheNS4B is a highly hydrophobic protein predicted to contain four transmembrane domains, while its N-terminal region may contribute to targeting of NS4B to intracellular membranes (29). Overexpression of NS4B in cell culture is sufficient to induce membrane alterations arguing that the main function of this protein is the formation of membranous structures serving as the scaffold of the HCV RC (30).…”
Section: Components Of the Hcv Replication Complexmentioning
confidence: 99%
“…NS4B: Inducer of a Membrane Scaffold for the Viral RC?-TheNS4B is a highly hydrophobic protein predicted to contain four transmembrane domains, while its N-terminal region may contribute to targeting of NS4B to intracellular membranes (29). Overexpression of NS4B in cell culture is sufficient to induce membrane alterations arguing that the main function of this protein is the formation of membranous structures serving as the scaffold of the HCV RC (30).…”
Section: Components Of the Hcv Replication Complexmentioning
confidence: 99%
“…Furthermore, it has been reported that the aminoterminal part of HCV-NS4B, containing the first 33 amino acids, has the ability to translocate at least partially towards the ER lumen. 13,15 Thus, bZIP-mediated NS4B protein interactions with other host and viral factors may depend on different localization of NS4B during the viral life cycle. Nevertheless, it must be discussed whether dimerization of NS4B is mediated solely by the bZIP motif or if other structural elements are involved.…”
Section: And Interaction Of Ns4b Proteins (C D) (A B)mentioning
confidence: 99%
“…Amongst others, bioinformatics was used to study protein structure and function as an alternative approach. 12,13 From several experimental and bioinformatics' analyses, it is accepted that NS4B contains at least four transmembrane domains (TMDs) in its middle part, while the topology of a putative fifth TMD close to the aminoterminal part remains controversial. [12][13][14][15] Furthermore, amphipathic a-helix structure elements were predicted within the aminoterminal part and recently reported to be potential targets of HCV replication inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations